2018
DOI: 10.18632/oncotarget.26035
|View full text |Cite
|
Sign up to set email alerts
|

Active ginseng components in cognitive impairment: Therapeutic potential and prospects for delivery and clinical study

Abstract: Cognitive impairment is a state that affects thinking, communication, understanding, and memory, and is very common in various neurological disorders. Among many factors, age-related cognitive decline is an important area in mental health research. Research to find therapeutic medications or supplements to treat cognitive deficits and maintain cognitive health has been ongoing. Ginseng and its active components may have played a role in treating chronic disorders. Numerous preclinical studies have confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 143 publications
(161 reference statements)
1
28
0
1
Order By: Relevance
“…In conclusion, natural active compounds show promising neuroprotective effects in several disease models. The potential of these compounds in terms of acting on GPCRs needs to be studied [5,6,200]. Several recent studies reported that nuclear receptor subfamily 4 group A member 2 [199], NACHT, LRR, and PYD domains containing protein 3 [201], and glutamate receptors [202] have great potential in neuroprotective therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, natural active compounds show promising neuroprotective effects in several disease models. The potential of these compounds in terms of acting on GPCRs needs to be studied [5,6,200]. Several recent studies reported that nuclear receptor subfamily 4 group A member 2 [199], NACHT, LRR, and PYD domains containing protein 3 [201], and glutamate receptors [202] have great potential in neuroprotective therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ginsenosides Rb1, Rg1, Rg2, Rg3, Ro, Rb3, Rd, Rf, Rh2, and 20(S)PT on the nervous system and the behavior of animals were demonstrated in numerous studies [3]. Ginsenosides Rb1, Rd, Re, Rg1, Rg2, Rg3, Rh1, Rh2, Rh3, PF11, and NTR1, gintonin, and compound K showed potential activity in treating cognitive deficits [41].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of different active ginseng compounds have been studied in both animals and humans 2 . The bioavailability of ginsenosides is low after oral administration, but the pharmacokinetic behavior differs among various ginsenosides 35,611 . The highly glycosylated ginsenosides Rb1, Rb2, Rc, Rd., Re, Rg1, and Rg2 have poor stability in the gastrointestinal tract, and they are easily converted into monoglycosides and aglycone ginsenosides (e.g., CK, Rh2, Rh1, and F1) by gastric acid and/or the intestinal flora 35,611–616 …”
Section: Challenges and Regulatory Issuesmentioning
confidence: 99%
“…Importantly, the term adaptogen is related to a physiological process—adaptation to environmental challenges, which is a multistep process including diverse mechanisms of extracellular and intracellular interactions. The renewed definition of adaptogens 16,17 is supported by the results of recent studies on the molecular mechanisms of action of adaptogens in a variety of regulatory systems from the cellular to entire organism levels 11,16–63 …”
Section: Introductionmentioning
confidence: 99%